FAKTOR YANG MEMPENGARUHI KREDIT BERMASALAH PADA BANK BUMN DAN NON BUMN YANG TERDAFTAR DI BEI TAHUN 2017-2021 - Rahman, Rahmita; -, Alfianti; Putri Sani, Andini; Isyana D. Pongoliu, Yayu (Politeknik Negeri Jakarta, 2023)
The purpose of this study was to analyze the influence of bank internal and external factors on NPL, the sample of this study was 32 banks listed on the Indonesian stock exchange. This study was analyzed using panel data. The data used in this study is secondary data, the data collection technique used is by collecting, recording, and reviewing secondary data in the form of annual financial reports of state-owned and non-state-owned banks which are published on the website of each bank. The data is obtained from the annual financial reports for 2017-2021. The results of this study indicate that the variables Return On Assets (ROA), Effect of Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) where these (three) variables have no significant effect on NPL. While the Capital Adequacy Ratio (CAR) variable has a significant effect on NPL.